Effects of performance evaluations on the quality of work life of employees: a review from 2008 to 2018 - Matabanchoy-Tulcán, Sonia Maritza; Álvarez-Pabón, Karol Melissa; Riobamba-Jiménez, Oscar David (Universidad y Salud, 2019)
Introduction: A Performance evaluations (PE) promotes personal-professional development and contributes to the improvement of the Quality of Work Life (QWL) of employees. A PE also enables the identification of strengths, generates self-evaluation processes and improves organizational development and competitiveness. Objective: To define the concept of performance evaluation and evaluate its effects on the quality of work life of employees from some sectors, during the last 10 years. Materials and methods: A systematic literature review using an integrative, observational and retrospective approach that included research studies sharing the same scope. We reviewed 55 articles published in databases such as Redalyc, SciELO, ScienceDirect and Dialnet. Results: We present and discuss the selection criteria, definition, and association between QWL and PE related to health, education and organizational sectors. Conclusions: The PE recognizes the contribution of the employee to the achievement of the organizational objectives and it takes into consideration the productivity, development and maintenance of the QWL of coworkers.